Molten Semiconductors for High Temperature Thermoelectricity. (1st January 2017) - Zhao, Youyang; Rinzler, Charles; Allanore, Antoine
Abstract : High temperature (>900°C) industrial waste heat recovery remains a key challenge for thermoelectric materials. The unique combination of high temperature, low heat-flux, and large surface area of waste heat generation as analyzed herein shows that active materials cost is the main metric inhibiting application. Molten compounds with semiconducting properties are therefore proposed as a cost-effective addition to solid-state materials for these conditions. A review of prior experimental results is presented, after which we demonstrate the performance of a laboratory-scale device based on molten SnS. The results allow reporting, for the first time, the Figure of Merit ( ZT ) and the conversion efficiency of the candidate materials. In addition, the Seebeck coefficient of molten SnS is reported. The results confirm the opportunity offered by molten thermoelectric compounds and allow discussion of the remaining materials and engineering challenges that need to be tackled in order to envision the future deployment of thermoelectric devices based on molten semiconductors.